Heart failure in human immunodeficiency virus-infected patients - O. G. Goryacheva; A. N. Koziolova (Российский кардиологический журнал)
Aim. To determine the features of heart failure (HF) development in patients with human immunodeficiency virus (HIV) infection.Material and methods. In a general hospital, 160 patients were examined during the year. All of them were divided into 2 groups: group 1 (n=100) — HIV-infected patients with specific clinical picture of HF; group 2 (n=60) — patients without HIV infection and with HF verified by echocardiography and concentration of N-terminal prohormone of brain natriuretic peptide (NT-proBNP).Results. In comparison with group 2, HIV-infected patients had the following statistically significant differences: lower left ventricular ejection fraction (LVEF), lower prevalence and severity of left ventricle diastolic dysfunction, higher LV mass index (LVMI), and lower NT-proBNP. HIV-infected patients had statistically significant moderate inverse relationship of LVEF (r=-0,43; p=0,015), E/e’ (r=-0,32; p=0,045), LVMI (r=-0,46; p=0,002) and strong relationship of NT-proBNP (r=-0,54; p<0,001) with CD4 T-lymphocyte count in 1 mm3 in the presence of HF symptoms and signs and an increase in NT-proBNP over 125 pg/ml. In group 1, there was a significantly higher prevalence of smoking, chronic alcoholism, drug use, chronic hepatitis C and cirrhosis (especially manifested by hepatomegaly and splenomegaly in combination with ascites and hepatic cytolysis), chronic pancreatitis, pneumonia and inflammatory diseases accompanied by higher erythrocyte sedimentation rate and C-reactive protein concentration, and lower hemoglobin level. HIV-infected patients were statistically less likely to use all groups of drugs for HF treatment, with the exception of spironolactone, and more likely to use drugs for multimorbidity treatment.Conclusion. The HF prevalence in hospitalized HIV-infected patients, estimated on the basis of symptoms and NT-proBNP increase >125 pg/ml, was 54%; on the basis of LVEF decrease <50% — 32%. The clinical picture of HIV-infected patients is characterized by various symptoms, including those typical for HF with normal NT-proBNP level, due to the high prevalence of comorbidities and concurrent medication.